THE USE OF SLANG LANGUAGE IN DAILY CONVERSATION AMONG TEENAGERS: DOES GENDER MATTER? - Saffa, Novelina Filzah Yuditya (ENGLISH JOURNAL, 2022)
Nowadays, slang words have now become part of teenagers' everyday language, since they use them in everyday speech. However, due to various of factors, there are disparities in the choice of slang phrases used by teenagers. Since the topic of gender's influence on language usage is not remarkably new, one of the factors that may have a large influence on the choice of slang words used is gender. Relying on this situation, the aims of this study are to investigate the types of slang words used by male and female teenagers, the influences of gender on the choice of slang words and the factors causing the differences. This study referred to the theory of types of slang words by Partridge (2004), gender theory by Diekman and Eagly's (2000), and ethnography of speaking theory by Hymes (1974). This study employed descriptive qualitative method. Observation and interview were employed during the study for the purpose of data collections. The participants of the study were 10 teenagers, 6 females and 4 males which are all college students in Surabaya. The analysis of the collected data revealed that English slang words that are commonly used by teenagers were identified as Society Slang. In addition to that, the investigation on the collected data also shows gender had no influence the choice of slang words. Lastly, the result of the study emphasized that the factors of how each person has their own choice of slang words are speech events which refers to Hymes' SPEAKING term.